2020
DOI: 10.5539/ies.v13n12p27
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support in the Relationship Between Adolescents’ Level of Loss and Grief and Well-Being

Abstract: In this study, the model, developed to examine the role of social support in the relationship between adolescents’ level of loss and grief and well-being, was tested. In this study, the descriptive research method was used, and its participants consisted of 216 adolescents who were high school students, in Turkey. Scales used in this study include Personal Information Form; Grief Scale; Five-Dimensional Well-Being Scale for Adolescents (EPOCH); Social Support Assessment Scale for Children and Adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Inadequate social support in grieving adolescents negatively affects adaptation and development. Savi Çakar (2020) states that a high level of social support facilitates adolescents' coping with loss and positively affects their level of well‐being. In the study, three of the participants in the pre‐action stated that they coped with social support indicates a positive situation in terms of adaptation to grief.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate social support in grieving adolescents negatively affects adaptation and development. Savi Çakar (2020) states that a high level of social support facilitates adolescents' coping with loss and positively affects their level of well‐being. In the study, three of the participants in the pre‐action stated that they coped with social support indicates a positive situation in terms of adaptation to grief.…”
Section: Discussionmentioning
confidence: 99%
“…A loved one or healthcare professional may, therefore, react in a negative way if they feel that the bereaved individual is violating the norm by not going through the stages. These reactions could result in bereaved people feeling alienated, an implication that is particularly worrying given that various studies have demonstrated the protective effect of social support in preventing negative effects in bereaved individuals (e.g., Hibberd et al, 2010 ; Çakar, 2020 ; Chen, 2020 ). Bereaved people themselves may also feel that there is something wrong with them for not grieving in line with the norm and may seek therapy to help move through the stages and grieve in the “correct” way.…”
Section: Discussionmentioning
confidence: 99%